An overview of food insecurity in Europe and what works and what doesn't work to tackle food insecurity. (30th September 2020) - Loopstra, R
Abstract: Data based on the FAO's Food Insecurity Experience Scale suggest prevalence rates as low as 3.1% in some countries, to more than 20% in others across Europe. In the past two decades, rising food bank use suggests a growing problem of severe food insecurity and is symptomatic of a lack of systematic governmental responses to hunger. In this absence, charities are often relied on to fill the gaps in the social security net. The pairing of the problem of hunger with the problem of food waste often fuels further development and entrenchment of charitable food redistribution through food banks, even though there is little evidence that these responses effectively reduce food insecurity. Research on the impacts of social security interventions, however, evidence the close links between these and food insecurity. How provision through social security systems can additionally accommodate the acquisition of sustainable and nutritious food is a challenge for the future, as current social security rates are often well below costs of living. These challenges reflect the need for systems thinking for tackling the challenges of sustainability, food insecurity, and low household incomes, underpinned by underemployment, low wages, unemployment, disability and caregiving.